BURNOUT SYMPTOMS AND VOCATIONAL BUSINESS EDUCATORS’ TURNOVER INTENTIONS: A STUDY OF NIGERIA’S PUBLIC UNIVERSITIES IN SOUTH-SOUTH (NAU Journal of Technology and Vocational Education, 2025)
On the bases of the theoretical and conceptual frameworks, the central aim of the study was twofold. First, it examines the levels of burnout with each symptom (i.e. exhaustion, mental distance, cognitive disorder and emotional disorder) and Vocational Business Educators’ turnover intentions. Second, the study tested a conceptual model that incorporates direct relationships between burnout with each symptom (i.e. exhaustion, mental distance, cognitive disorder and emotional disorder) and Vocational Business Educators’ turnover intentions. A quantitative research design was adopted toactualize the aim of this study. The participants consisted of 138 Vocational Business Educators from 13 Nigeria’s Public Universities in South-South. The authors applied descriptive statistics (e.g. Mean and Standard Deviation), and inferential statistics (e.g. Spearman's rho correlation and linear regression via 10000 resamples bootstrap estimate). The results showed that the levels ofburnout with each symptom (i.e. exhaustion, mental distance, cognitive disorder and emotional disorder) and Vocational Business Educators’ turnover intention were very high. The results further showed that burnout with each symptoms (i.e. exhaustion, mental distance, cognitive disorder and emotional disorder) were significant positive predictors of Vocational Business Educators’ turnover intentions. Furthermore, limitations of the study and implications of the results were discussed.
Keywords: Burnout Symptoms; public universities; turnover Intentions; vocational business educator